1998
DOI: 10.1046/j.1365-2958.1998.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Antisense inhibition of expression of cysteine proteinases does not affect Entamoeba histolytica cytopathic or haemolytic activity but inhibits phagocytosis

Abstract: SummaryInhibition of most of the expression of the cysteine proteinases of Entamoeba histolytica strain HM-1: IMSS was successfully performed by transcription of ehcp5 antisense RNA using the promoter of ehg34, which encodes a L21 ribosomal protein of E. histolytica. We have generated a stable transfectant in which the overall level of cysteine proteinase activity is strongly reduced (Ϸ 90%). This transfectant has a normal growth rate in Diamond's TYI-S-33 medium, a cytopathic and haemolytic activity similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 32 publications
4
118
2
Order By: Relevance
“…Cysteine protease activity is necessary for the trophozoites to traverse a colonic mucus barrier before cell cytolysis (8,16). In addition, the proteases are necessary for the parasite to disrupt the epithelial cell monolayers in vitro (15), to disseminate through host tissue (26), and to cause liver abscesses (27,28). The mechanism by which the parasite disrupts and penetrates the mucin polymeric network was previously unknown, but recent evidence suggests that the amoeba disrupts the MUC2 polymers (8).…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine protease activity is necessary for the trophozoites to traverse a colonic mucus barrier before cell cytolysis (8,16). In addition, the proteases are necessary for the parasite to disrupt the epithelial cell monolayers in vitro (15), to disseminate through host tissue (26), and to cause liver abscesses (27,28). The mechanism by which the parasite disrupts and penetrates the mucin polymeric network was previously unknown, but recent evidence suggests that the amoeba disrupts the MUC2 polymers (8).…”
Section: Discussionmentioning
confidence: 99%
“…This fragment was then inserted into plasmid pSA8 (17) replacing the antisense ehcp5 insert to create pZZ1. 1 ϫ 10 7 E. histolytica HM1:1MSS trophozoites in log phase growth were transfected with 100 ng of plasmid pZZ1, pSA8 (antisense construct against E. histolytica cysteine proteinase 5), or the parent pNeo-Act plasmid without an insert (17). Selection was performed by adding 10 g/ml G418 to TYI-S33 media beginning 48 h after transfection and gradually increasing G418 concentration to 50 g/ml over 2 weeks' time.…”
Section: Methodsmentioning
confidence: 99%
“…Amebic lysates derived from pZZ1-transfected trophozoites had 30% of the ADH activity of lysates derived from equivalent numbers of wild type HM1:IMSS trophozoites or trophozoites transformed with plasmid pSA8 (which contains an antisense transcript to the E. histolytica cysteine proteinase 5 gene) (Table I) (17). Using immunoblotting with antiserum raised against EhADH2, we found that EhADH2 was present in lower amounts (83% reduction by scanning densitometry of the autoradiograph bands) in SDS-PAGE-separated lysates from pZZ1-transfected E. histolytica compared with lysates from pSA8-transfected E. histolytica (Fig.…”
Section: Episomal Expression Of An Antisense Rna To the Ehadh2mentioning
confidence: 99%
“…Although targeted disruption of selected E. histolytica genes has not yet been achieved, stable episomal expression of foreign DNA is possible in amoebae by maintaining continuous selective pressure [Hamann et al 1995, Vines et al 1995. This has enabled the investigators to target specific molecules in E. histolytica by the episomal expression of antisense mRNA or of genes encoding dominant negative mutants [Ankri et al 1998]. The antisense approach has been applied to E. histolytica cysteine proteinases and episomal expression of an antisense RNA to ehcp5 could reduce total amoebic proteinase activity by 80-90% [Ankri et al 1998].…”
Section: Mechanisms Of Hepatocellular Dysfunction and Regeneration: Ementioning
confidence: 99%
“…This has enabled the investigators to target specific molecules in E. histolytica by the episomal expression of antisense mRNA or of genes encoding dominant negative mutants [Ankri et al 1998]. The antisense approach has been applied to E. histolytica cysteine proteinases and episomal expression of an antisense RNA to ehcp5 could reduce total amoebic proteinase activity by 80-90% [Ankri et al 1998]. To assess the role of E. histolytica cysteine proteinases in amoebiasis, in earlier study, human xenografts in SCID-HU-INT mice were infected with amoebic trophozoites expressing the ehcp5 antisense RNA(proteinase-deficient amoebae) or amoebic trophozoites containing the same plasmid without the antisense insert (the control group) [Zhang et al 2000].…”
Section: Mechanisms Of Hepatocellular Dysfunction and Regeneration: Ementioning
confidence: 99%